Hubungan Tonsilektomi dengan Umur Keluhan Utama dan Ukuran Tonsil pada Pasien Tonsilitis Kronik - Festy Ladyani Mustofa; Femina Susanti; Aziza (ARTERI : Jurnal Ilmu Kesehatan, 2020)
Chronic tonsillitis is a recurring infection that most often occurs in the throat, especially in children and adolescents. Tonsillectomy is one type of Ear Nose Throat (ENT) surgery that is most often performed on children, adolescents and adults. Tonsillectomy is also a procedure that can be done if there is a chronic infection or a recurring infection. Factors that can affect tonsillectomy are age, major complaints and size of the tonsils. This study was conducted to determine the relationship of tonsillectomy with age, major complaints and the size of tonsils in chronic tonsillitis patients in RSPBA of Lampung city in 2018-2019. This study uses cross-sectional, quantitative, analytic methods with secondary tonsillitis data collection. Sampling uses a total sampling technique. Data collection was done by recording data in the form of major complaints, age and size of the tonsils and analyzed using the chi-square test. The results showed that 109 tonsillitis patients showed that the majority of tonsillitis patients were group: age ≤ 18 years as many as 73 people, tonsillectomy was 66 people (90.4%), main complaints >1 were 90 people, tonsillectomy was 83 people (83 people) 92.2%) and T3-T4 tonsil size of 70 people, with tonsillectomy of 65 people (92.2%). The results also showed that there was a relationship between tonsillectomy between age (p = 0.01, OR = 3.626), main complaints (p = 0.00, OR = 13.175), tonsil size (p = 0.00, OR = 5.778) in chronic tonsilits patients at RSPBA Bandar Lampung in 2018-2019. This study concluded that there was a significant relationship between tonsillectomy with age, major complaints and the size of tonsils in chronic tonsillitis patients in Bandar Lampung RSPBA 2018-2019 with a p-value <0.05.